2018
DOI: 10.3847/1538-4357/aae488
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy Structure, Stellar Populations, and Star Formation Quenching at 0.6 ≲ z ≲ 1.2

Abstract: We use both photometric and spectroscopic data from the Hubble Space Telescope to explore the relationships among 4000 Å break (D4000) strength, colors, stellar masses, and morphology, in a sample of 352 galaxies with log(M * /M ⊙ ) > 9.44 at 0.6 z 1.2. We have identified authentically quiescent galaxies in the UV J diagram based on their D4000 strengths. This spectroscopic identification is in good agreement with their photometrically-derived specific star formation rates (sSFR). Morphologically, most (that i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 134 publications
4
23
0
Order By: Relevance
“…A natural consequence of this is that the B/T (and also more generally the Sérsic index and light concentration which measures similar properties) ratio of galaxies is correlated with f Q , as we show in Fig. 8 (see also Kim et al 2018).…”
Section: Structural Dependence Predicted From the Quiescent Fractionsupporting
confidence: 62%
See 1 more Smart Citation
“…A natural consequence of this is that the B/T (and also more generally the Sérsic index and light concentration which measures similar properties) ratio of galaxies is correlated with f Q , as we show in Fig. 8 (see also Kim et al 2018).…”
Section: Structural Dependence Predicted From the Quiescent Fractionsupporting
confidence: 62%
“…Overall we find quiescent galaxies to have higher values of B/T than star-forming galaxies at stellar masses greater than 10 10 M , which is expected given the more bulge-dominated nature of quiescent galaxies (e.g. Wuyts et al 2011;Kim et al 2018;Morselli et al 2019). Regarding the trend with stellar mass, we find that both quiescent and star-forming systems show an increase of B/T with increasing stellar mass (weak, non-negligible correlation -<1% -likely of being an uncorrelated distribution).…”
Section: Prominence Of Galactic Bulgessupporting
confidence: 56%
“…The specific star formation rate (sSFR), defined as star formation rate normalized by stellar mass, is a powerful summary statistic for the level of star formation in galaxies (e,g., Whitaker et al 2012;Kim et al 2018). Since the power available to drive galactic winds increases with increasing star formation, while the escape velocity for such winds increases with stellar mass, it is reasonable to expect galactic scale outflows to be more common and stronger where sSFR is high.…”
Section: Examining Specific Star Formation Intensitymentioning
confidence: 99%
“…At 𝑧 < 1, many studies have reported a positive correlation between D n 4000 and stellar mass (e.g. Brinchmann et al 2004;Moresco et al 2010Moresco et al , 2011Moresco et al , 2016Haines et al 2017;Siudek et al 2017;Kim et al 2018;Wu et al 2018a). This has been widely associated with the "downsizing" trend, in which the stellar populations of more massive galaxies formed earlier in cosmic history, with present-day star formation concentrated in lower-mass galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%